2017
DOI: 10.1136/neurintsurg-2017-013350
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of effectiveness of preoperative embolization in surgery for metastatic spine disease

Abstract: PE can be effective in reducing IBL in spinal metastases surgery in both renal cell carcinoma and mixed primary tumor groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 11 publications
2
28
0
1
Order By: Relevance
“…For the spinal metastasis of hyper-vascular tumors, such as renal cell, hepatocellular, and thyroid cancers, preoperative embolization is recommended. Previous studies have verified the effectiveness of preoperative embolization in reducing intraoperative bleeding in spinal metastasis surgeries [85][86][87]. Surgery should be performed within 24 hours following embolization to avoid the diminished effect of preoperative embolization [88].…”
Section: Postoperative Complications and Preventive Measuresmentioning
confidence: 99%
“…For the spinal metastasis of hyper-vascular tumors, such as renal cell, hepatocellular, and thyroid cancers, preoperative embolization is recommended. Previous studies have verified the effectiveness of preoperative embolization in reducing intraoperative bleeding in spinal metastasis surgeries [85][86][87]. Surgery should be performed within 24 hours following embolization to avoid the diminished effect of preoperative embolization [88].…”
Section: Postoperative Complications and Preventive Measuresmentioning
confidence: 99%
“…In the present study, we compared the IBL during surgery for spinal metastases in patients undergoing or not undergoing PE and drew a different conclusion from the authors of a previous meta-analysis (18). A reduction in IBL after embolization was only observed during surgery for spinal metastases of hypervascular tumors determined as such using angiographic evidence.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, the role of PE for spinal metastases remains controversial. A meta-analysis, conducted by Luksanapruksa et al (18), included five studies conducted between 1993 and 2015. They concluded that PE could be useful in reducing IBL in surgery for spinal metastases of both renal cell carcinoma and mixed tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Bir meta-analize göre, hipervasküler spinal metastaz cerrahisinde ameliyat öncesi embolizasyon, ameliyat sırasındaki ortalama kan kaybını 1226 mL azaltarak anlamlı bir fark ortaya koymuştur. [19] Kato ve ark., tiroid karsinomlarına bağlı spinal metastazların ameliyat öncesi embolizasyon sonrası,…”
Section: Spinal Metastazların Cerrahi Tedavisiunclassified